Development of Turn-milling in Conventional Lathe Machine - Yohanes, Yohanes; Handika, Roki; Jefryanto, Gusmardani; Yulianto, Evon (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
Turn-milling is a machining method with a system of merging turning and milling operations, which the workpieces and cutting tool perform rotary motion synchronously to optimize the disposal process of chip materials. Development of turn-milling can be done on the lathe and milling conventional machining. The purpose of this study is to modify a conventional lathe with a stationary cutting tool and use a single cutting edge into a rotary tool using 4 (four) cutting sides (multy point cutting). In the manufacture and installation of rotary tool on conventional lathes, tools are made portable and can work on tangential, orthogonal and co-axial turn-milling systems. For the orthogonal and co-axial operating system of the turn-milling are divided into up and down operating systems. In this research the phenomenon of material disposal process of the work-piece surface was investigated. In the process of turn-milling test, the chip was removed automatically as the turn of the cutting edge of the endmill cutting tool. The high decreasing of cutting knife rotation during testing was resulted a space during the process of disposal of material. Sequence, it was occurred pores or cavities in the work-piece.